Assumptions, conjectures, and other miracles: The application of evaluative thinking to theory of change models in community development. (December 2016) - Archibald, Thomas; Sharrock, Guy; Buckley, Jane; Cook, Natalie
Highlights: An evaluation capacity building approach designed to foster evaluative thinking (ET) is described. The approach has been piloted with Catholic Relief Services in Ethiopia and Zambia. Community development practitioners learn to apply ET to work with assumptions in their theory of change models. Initial evidence suggests that this approach can help foster reflective practice and adaptive program management. Abstract: Unexamined and unjustified assumptions are the Achilles' heel of development programs. In this paper, we describe an evaluation capacity building (ECB) approach designed to help community development practitioners work more effectively with assumptions through the intentional infusion of evaluative thinking (ET) into the program planning, monitoring, and evaluation process. We focus specifically on one component of our ET promotion approach involving the creation and analysis of theory of change (ToC) models. We describe our recent efforts to pilot this ET ECB approach with Catholic Relief Services (CRS) in Ethiopia and Zambia. The use of ToC models, plus the addition of ET, is a way to encourage individual and organizational learning and adaptive management that supports more reflective and responsive programming.